High-performance and high-stability closed-loop recyclable thermosetting resin, and preparation method and recycling method thereof

CN121591977BActive Publication Date: 2026-10-20QINGDAO UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511674522.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-10-20
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

然而超分子与共价网络的构建通常依赖于多种不同类型的键合方式,或需要动态共价与非共价作用之间实现正交聚合,导致材料的合成与制备过程较为复杂

Benefits of technology

优选地,有机溶剂为N, N-二甲基甲酰胺、二甲基亚砜中的一种或两种;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a high-performance and high-stability closed-loop recyclable thermosetting resin and a preparation method and a recycling method thereof. In the application, a monomer is a multifunctional aldehyde compound and thiohydrazide, and a crosslinking network containing a thiohydrazide bond is obtained through condensation reaction. Since the thiohydrazide bond can form a zigzag hydrogen bond, and the benzene rings on the polymer main chain can form a π-π conjugated structure, the interchain supramolecular interaction further increases the strength and toughness of the resin, and at the same time, the resin is endowed with excellent stability. The thiohydrazide bond can undergo transamination reaction under the induction of thiohydrazide, and the obtained resin can be depolymerized in a mixed system of an organic solvent containing thiohydrazide. Fresh multifunctional aldehyde compounds are added in the application, and the recycled resin with performance equivalent to the original crosslinking network can be regenerated in situ.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sustainable development of polymer materials, specifically to a high-performance, high-stability, closed-loop recyclable thermosetting resin and its preparation and recycling methods. Background Technology

[0002] Thermosetting resins, due to their three-dimensional cross-linked network structure, exhibit excellent mechanical properties, thermal stability, dimensional stability, and solvent resistance. Therefore, they are widely used in transportation, aerospace, and composite materials. However, because thermosetting resins have permanent cross-linked networks, once fully cured, they are extremely difficult to reprocess, recycle, and remodel, making them difficult to recycle after disposal. The main disposal methods for thermosetting resins are incineration and landfill, which exacerbate environmental pollution, severely restrict their sustainable development, and lead to environmental challenges. Introducing dynamic covalent bonds into thermosetting resins to generate dynamic covalent networks allows for dynamic covalent bond exchange and rearrangement triggered by external stimuli, resulting in a rearrangement of their network topology. This provides an effective method for the recyclability and / or reprocessability of thermosetting resins, thereby alleviating the resource crisis and environmental pollution problems faced by thermosetting resins.

[0003] To date, most dynamic covalent networks often face a trade-off between performance and recyclability; achieving both high efficiency and high performance simultaneously remains a significant challenge. Many current methods enhance bond exchange kinetics by reducing crosslink density or employing more flexible structural designs, but often at the expense of mechanical properties. Furthermore, exchange mechanisms relying on nucleophiles (such as hydroxyl, amino, or thiol groups) or catalysts may trigger side reactions such as hydrolysis or decomposition, leading to material degradation and thus limiting their practical applications.

[0004] Currently, the introduction of supramolecular interactions (such as hydrogen bonding, π–π stacking, and metal-ligand coordination) into synthetic materials can effectively dissipate energy through rapid breakage and reconstruction in response to stimuli, thereby enhancing and toughening polymers. However, the construction of supramolecular and covalent networks often relies on various types of bonding mechanisms or requires orthogonal polymerization between dynamic covalent and non-covalent interactions, leading to complex synthesis and preparation processes. Furthermore, the inherent instability of dynamic non-covalent and dynamic covalent bonds continues to limit their environmental durability and practical applications. Summary of the Invention

[0005] In view of this, the present invention provides a high-performance, high-stability, closed-loop recyclable thermosetting resin, its preparation method, and its recycling method. Using polyfunctional aldehyde compounds and thiohydrazides as raw materials, the present invention obtains a novel thermosetting resin with dynamic thiourea bonds through a solution film-forming method. This resin possesses both high thermal and mechanical properties, and utilizes the dynamic nature of the thiourea bonds to achieve hot-press remolding and closed-loop recycling, providing an effective method for the recyclability and / or reprocessability of high-performance thermosetting materials.

[0006] The technical solution of the present invention is as follows: This invention provides a high-performance, high-stability, closed-loop recyclable thermosetting resin, the preparation method of which includes the following steps: (1) Using p-hydroxybenzaldehyde as a raw material, prepare difunctional aldehyde compounds with different substituents; (2) Dissolve the dialdehyde compound prepared in step (1) and commercial pyromellitic methyl ether in an organic solvent, add thiodihydrazide monomer, stir evenly, and then solidify the solution to obtain the thermosetting resin.

[0007] Preferably, the difunctional aldehyde compound has one or more of the following structural formulas:

[0008] Preferably, the thiodihydrazide monomer has any of the following structural formulas:

[0009] Preferably, the organic solvent is one or more of methanol, N,N-dimethylformamide, and dimethyl sulfoxide.

[0010] The molar ratio of the aldehyde group to the amine group in the thiodihydrazide monomer of the polyaldehyde compound is 1:1 to 1:0.8.

[0011] Preferably, the reaction temperature of the thiourea is 65~150 °C and the time is 4~6 h.

[0012] This invention provides a method for recycling the high-performance, high-stability, closed-loop recyclable thermosetting resin obtained by the above preparation method, comprising the following steps: High-performance, high-stability, and recyclable thermosetting resin is immersed in a solvent to fully swell, then hot-pressed and molded, and finally the solvent is dried to obtain remolded resin. Preferably, the solvent is one or two of N,N-dimethylformamide and dimethyl sulfoxide; Preferably, the hot pressing conditions are 140~160 °C, 20~30 min, and 10~15 MPa.

[0013] A high-performance, high-stability, and recyclable closed-loop thermosetting resin is immersed in an organic solvent containing thiohydrazide monomer to carry out a depolymerization reaction, resulting in a resin solution. Then, a fresh aldehyde compound is added, and the closed-loop recyclable thermosetting resin can be re-prepared according to the preparation method of high-performance, high-stability, and recyclable closed-loop thermosetting resin. Preferably, the organic solvent is one or both of N,N-dimethylformamide and dimethyl sulfoxide; Preferably, the mass ratio of the thiohydrazide monomer to the resin is 2:1 to 3:1; Preferably, the molar ratio of the added fresh aldehyde compound to the aldehyde and amino groups of the depolymerized thiohydrazine monomer is 1:1 to 1:0.8.

[0014] This invention provides a high-performance, high-stability, closed-loop recyclable thermosetting resin, prepared by a condensation reaction between a polyaldehyde compound and a thiohydrazide compound at a molar ratio of aldehyde to amino groups of 1:1 to 1:0.8, to form a thiourea bond, thus obtaining a cross-linked polymer. Due to the abundant aromatic ring structure, π–π stacking, and high-density hydrogen bonds in the cross-linked network, the resin possesses high thermal and mechanical properties and excellent water resistance. Simultaneously, the thiourea bond, benzene ring, and carbon-nitrogen double bond form a conjugated structure, making it difficult for the carbon-nitrogen double bond to be protonated, further increasing the resin's strength and toughness, while also endowing the resin with excellent acid resistance and creep resistance.

[0015] This invention provides a method for preparing the above-mentioned high-performance, high-stability, and closed-loop recyclable thermosetting resin. This invention obtains the high-performance, high-stability, and closed-loop recyclable thermosetting resin through thiourea condensate bonds. This method is simple to operate, low in cost, and easy to realize industrial mass production.

[0016] This invention provides a method for recovering the aforementioned high-performance, high-stability, closed-loop recyclable thermosetting resin. In this invention, the dynamic nature of thiourea bonds allows for the reprocessing and recovery of the cross-linked network to obtain reconstituted resin. The high-performance, high-stability, closed-loop recyclable thermosetting resin of this invention can also be recovered through solution depolymerization. The thiourea bonds can undergo transamination, depolymerizing into an oligomer solution under the induction of a thiohydrazide monomer. By adding a fresh aldehyde compound, a new thiourea cross-linked network can be regenerated. The regenerated thermosetting resin obtained by these two recovery methods still possesses high thermal and mechanical properties, as well as water and acid resistance, achieving closed-loop recovery under mild conditions. Attached Figure Description

[0017] Figure 1 This is a physical image of the plastic object from Embodiment 1 of the present invention; Figure 2 The stress-strain curves of the plastics in Examples 1-3 of this invention are shown. Figure 3 This is the closed-loop recycling process for plastics in Embodiment 2 of the present invention; Figure 4 This is an organic solvent resistance test of the plastic in Example 3 of the present invention; Figure 5 The stress-strain curve of the plastic in Example 3 of the present invention after multiple closed-loop recycling is shown. Detailed Implementation

[0018] The following detailed description, in conjunction with embodiments, illustrates the high-performance, high-stability, closed-loop recyclable thermosetting resin and its preparation and recycling methods provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.

[0019] Example 1 p-Hydroxybenzaldehyde (13.6 g, 0.11 mol) and anhydrous potassium carbonate (15.4 g, 0.11 mol) were dissolved in anhydrous N,N-dimethylformamide at 60 °C. 1,4-Dibromobutane (10 g, 0.05 mol) was added to anhydrous N,N-dimethylformamide and dissolved at 60 °C. The mixture was reacted at 90 °C for 12 h to obtain the product 4,4'-(butane-1,4-diyloxy)dibenzaldehyde. The crude product was washed with deionized water and isopropanol, filtered, and dried to obtain pure 4,4'-(butane-1,4-diyloxy)dibenzaldehyde, with an overall yield of 89%.

[0020] Trimethylbenzaldehyde (0.15 g, 0.93 mmol) and 4,4'-(butane-1,4-dimethyloxy)dibenzaldehyde (0.28 g, 0.93 mmol) were added to a 10 mL reaction flask and dissolved in 1 mL of N,N-dimethylformamide at 80 °C. Thiodiazid (0.25 g, 2.4 mmol) was added to a 10 mL reaction flask and dissolved in 1.5 mL of dimethyl sulfoxide and 0.5 mL of N,N-dimethylformamide at 80 °C. After both were dissolved, the mixture was reacted at 80 °C until a high-viscosity prepolymer was formed. This prepolymer was then rapidly cast into a film on a constant-temperature heating stage at 100 °C. After 30 min, the film was vacuum-cured at 100 °C and 120 °C for 2 h, respectively, to obtain a crosslinked network.

[0021] The actual image of the obtained plastic film is shown below. Figure 1 As shown, by Figure 1 It can be seen that the plastic film prepared by this invention has good transparency.

[0022] The glass transition temperature of the obtained resin film, as measured by a thermodynamic mechanical analyzer, is 217 °C, indicating high thermal properties.

[0023] The tensile strength of the obtained resin film was tested using a universal testing machine. The test results showed that the tensile strength of the obtained plastic film was 91.4 MPa, which belongs to the category of high tensile strength and high toughness resin.

[0024] The obtained plastic film was immersed in water, organic solvents (ethanol, tetrahydrofuran, dimethyl sulfoxide), and 1 M hydrochloric acid to test its water resistance and solvent resistance. The tests showed that the obtained resin film exhibited good resistance in water, various organic solvents, and hydrochloric acid, and did not dissolve or depolymerize even after 7 days of immersion.

[0025] A recycling method for high-strength, solvent-resistant, and closed-loop recyclable plastics employs the following steps: The resin film obtained in Example 1 was cut into fragments and placed in dimethyl sulfoxide. The swollen resin fragments were then placed in a flat vulcanizing machine for hot pressing to obtain a reshaped resin film.

[0026] The resin film prepared in Example 1 was cut into fragments and placed in dimethyl sulfoxide containing thiohydrazide monomer. The resin underwent depolymerization and dissolution. Then, a new aldehyde compound was added to the solution, and the reaction was carried out at 80 °C to form a high-viscosity solution. Subsequently, it was rapidly cast into a film on a constant temperature heating stage at 100 °C. After 30 min, it was vacuum cured at 100 °C and 120 °C for 2 h respectively to obtain a regenerated crosslinked network, thus achieving closed-loop recycling.

[0027] Example 2 p-Hydroxybenzaldehyde (10.8 g, 0.09 mol) and anhydrous potassium carbonate (12.2 g, 0.09 mol) were dissolved in anhydrous N,N-dimethylformamide at 60 °C. 1,8-Dibromooctane (10 g, 0.04 mol) was added to anhydrous N,N-dimethylformamide and dissolved at 60 °C. The mixture was reacted at 90 °C for 12 h to give 4,4'-(octane-1,8-diyloxy)dibenzaldehyde. The crude product was washed with deionized water and isopropanol, filtered, and dried to give pure 4,4'-(octane-1,8-diyloxy)dibenzaldehyde in an overall yield of 86%.

[0028] Trimethylbenzaldehyde (0.15 g, 0.93 mmol) and 4,4'-(octane-1,8-dimethyloxy)dibenzaldehyde (0.33 g, 0.93 mmol) were added to a 10 mL reaction flask and dissolved in 1 mL of N,N-dimethylformamide at 80 °C. Thiodiazid (0.25 g, 2.4 mmol) was added to a 10 mL reaction flask and dissolved in 1.5 mL of dimethyl sulfoxide and 0.5 mL of N,N-dimethylformamide at 80 °C. After both were dissolved, the mixture was reacted at 80 °C until a high-viscosity prepolymer was formed. This prepolymer was then rapidly cast into a film on a 100 °C isothermal heating stage. After 30 min, the film was vacuum cured at 100 °C and 120 °C for 2 h, respectively, to obtain a crosslinked network.

[0029] The actual image of the obtained plastic film is shown below. Figure 1 As shown, by Figure 1 It can be seen that the plastic film prepared by this invention has good transparency.

[0030] The glass transition temperature of the obtained resin film, as measured by a thermodynamic mechanical analyzer, is 212 °C, indicating high thermal properties.

[0031] The tensile strength of the obtained resin film was tested using a universal testing machine. The test results showed that the tensile strength of the obtained plastic film was 127.1 MPa, which belongs to the category of high tensile strength and high toughness resin.

[0032] The obtained plastic film was immersed in water, organic solvents (ethanol, tetrahydrofuran, dimethyl sulfoxide), and 1 M hydrochloric acid to test its water resistance and solvent resistance. The tests showed that the obtained resin film exhibited good resistance in water, various organic solvents, and hydrochloric acid, and did not dissolve or depolymerize even after 7 days of immersion.

[0033] A recycling method for high-strength, solvent-resistant, and closed-loop recyclable plastics employs the following steps: The resin film obtained in Example 2 was cut into fragments and placed in dimethyl sulfoxide. The swollen resin fragments were then placed in a flat vulcanizing machine for hot pressing to obtain a reshaped resin film.

[0034] The resin film prepared in Example 2 was cut into fragments and placed in dimethyl sulfoxide containing thiohydrazide monomer. The resin underwent depolymerization and dissolution. Then, a new aldehyde compound was added to the solution, and the reaction was carried out at 80 °C to form a high-viscosity solution. Subsequently, it was rapidly cast into a film on a constant temperature heating stage at 100 °C. After 30 min, it was vacuum cured at 100 °C and 120 °C for 2 h respectively to obtain a regenerated crosslinked network, thus achieving closed-loop recycling.

[0035] Example 3: p-Hydroxybenzaldehyde (8.9 g, 0.073 mol) and anhydrous potassium carbonate (10.1 g, 0.073 mol) were dissolved in anhydrous N,N-dimethylformamide at 60 °C. 1,12-Dibromododecane (10 g, 0.03 mol) was added to anhydrous N,N-dimethylformamide and dissolved at 60 °C. The mixture was reacted at 90 °C for 12 h to give 4,4'-(dodecane-1,12-diyloxy)dibenzaldehyde. The crude product was washed with deionized water and isopropanol, filtered, and dried to give pure 4,4'-(dodecane-1,12-diyloxy)dibenzaldehyde in an overall yield of 87%.

[0036] Trimethylbenzaldehyde (0.15 g, 0.93 mmol) and 4,4'-(dodecane-1,12-dimethyloxy)dibenzaldehyde (0.39 g, 0.93 mmol) were added to a 10 mL reaction flask and dissolved in 1 mL of N,N-dimethylformamide at 80 °C. Thiodiazid (0.25 g, 2.4 mmol) was added to a 10 mL reaction flask and dissolved in 1.5 mL of dimethyl sulfoxide and 0.5 mL of N,N-dimethylformamide at 80 °C. After both were dissolved, the mixture was reacted at 80 °C until a high-viscosity prepolymer was formed. This prepolymer was then rapidly cast into a film on a 100 °C isothermal heating stage. After 30 min, the film was vacuum cured at 100 °C and 120 °C for 2 h, respectively, to obtain a crosslinked network.

[0037] The actual image of the obtained plastic film is shown below. Figure 1 As shown, by Figure 1 It can be seen that the plastic film prepared by this invention has good transparency.

[0038] The glass transition temperature of the obtained resin film, as measured by a thermodynamic mechanical analyzer, is 196 °C, indicating high thermal properties.

[0039] The tensile strength of the obtained resin film was tested using a universal testing machine. The test results showed that the tensile strength of the obtained plastic film was 104.3 MPa, which belongs to the category of high tensile strength and high toughness resin.

[0040] The obtained plastic film was immersed in water, organic solvents (ethanol, tetrahydrofuran, dimethyl sulfoxide), and 1 M hydrochloric acid to test its water resistance and solvent resistance. The tests showed that the obtained resin film exhibited good resistance in water, various organic solvents, and hydrochloric acid, and did not dissolve or depolymerize even after 7 days of immersion.

[0041] A recycling method for high-strength, solvent-resistant, and closed-loop recyclable plastics employs the following steps: The resin film obtained in Example 3 was cut into fragments and placed in dimethyl sulfoxide. The swollen resin fragments were then placed in a flat vulcanizing machine for hot pressing to obtain a reshaped resin film.

[0042] The resin film prepared in Example 3 was cut into fragments and placed in dimethyl sulfoxide containing thiohydrazide monomer. The resin underwent depolymerization and dissolution. Then, a new aldehyde compound was added to the solution, and the reaction was carried out at 80 °C to form a high-viscosity solution. Subsequently, it was rapidly cast into a film on a constant temperature heating stage at 100 °C. After 30 min, it was vacuum cured at 100 °C and 120 °C for 2 h respectively to obtain a regenerated crosslinked network, thus achieving closed-loop recycling.

[0043] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A depolymerization method for a high-performance, high-stability, closed-loop recyclable thermosetting resin, characterized in that, The preparation method of the high-performance, high-stability, closed-loop recyclable thermosetting resin includes the following steps: (1) Using p-hydroxybenzaldehyde as a raw material, prepare difunctional aldehyde compounds with different substituents; (2) Dissolve the dialdehyde compound prepared in step (1) and pyromellitic methyl ester in an organic solvent, add thiodihydrazide monomer, stir evenly, and then solidify the solution to obtain the thermosetting resin. The difunctional aldehyde compound has one or more of the following structural formulas: ; The depolymerization method for the high-performance, high-stability, closed-loop recyclable thermosetting resin includes the following steps: Thermosetting resin is immersed in an organic solvent containing thiohydrazide monomers to carry out a depolymerization reaction, resulting in a resin solution. Fresh aldehyde compound is then added, and closed-loop recycled thermosetting resin can be prepared again according to the aforementioned method for preparing thermosetting resin.

2. The depolymerization method for high-performance, high-stability, closed-loop recyclable thermosetting resin according to claim 1, characterized in that, The structural formula of the thiodiazid monomer is any one of the following: 。 3. The depolymerization method for high-performance, high-stability, closed-loop recyclable thermosetting resin according to claim 1, characterized in that, The molar ratio of the aldehyde group to the amine group in the thiodihydrazide monomer in step (2) is 1:

1.

4. The depolymerization method for high-performance, high-stability, closed-loop recyclable thermosetting resin according to claim 1, characterized in that, The temperature of the thiourea reaction in step (2) is 65~150 ℃ and the time is 4~6 h.

Citation Information

Patent Citations

  • Intrinsic self-repairing and recyclable polythiourea polymer, and preparation method and application thereof

    CN110551274A